STRATEGY OF THE NATIONAL UNITY AND POLITICS AGENCY (KESBANGPOL) IN HANDLING SOCIAL CONFLICT AMONG POLITICAL PARTY SUPPORTERS IN PESAWARAN REGENCY - Hengki Wijaya; Malik (International Journal of Multidisciplinary Reseach, 2026)
This study used a descriptive qualitative research method. The method was applied to describe and qualitatively examine the strategy of the National Unity and Politics Agency (Kesbangpol) in handling social conflict among political party supporters in Pesawaran Regency. All data were obtained directly from field informants through interviews and document studies. The findings show that: (1) in the strategy formulation dimension, conflict-handling steps were prepared by considering potential political vulnerabilities in the community. Strategy formulation was conducted through problem identification, mapping of conflict-prone areas, monitoring of political situations, and coordination with related parties; (2) in the strategy implementation dimension, early detection, community political education, cross-sector coordination, dialogue facilitation, mediation, and public appeals to maintain political conduciveness were carried out; and (3) in the strategy evaluation dimension, Kesbangpol assessed the implementation of strategies through situational monitoring, activity reporting, and evaluation of conflict-handling effectiveness. The inhibiting aspects include limited data at the formulation stage, coordination constraints and political fanaticism at the implementation stage, and weak measurement and follow-up at the evaluation stage.